A thirteen year old female with primary T-cell rich B-cell lymphoma of bone masquerading as chronic recurrent multifocal osteomyelitis - Saadiya Haque (MDPI AG, 2009)
Primary lymphoma of the bone (PLB) accounts for 2% of all non-Hodgkin's lymphomas, and until recently it had not been well characterized in literature. Most cases present in adulthood (average age 50), with localized painful lesions in the long bones, cranium, or axial skeleton. We describe a case of multifocal PLB in an adolescent female. In this case, the initial presentation, with migratory large joint polyarthralgias and bone pain, mimicked chronic recurrent multifocal osteomyelitis (CRMO). Had a biopsy not been performed the diagnosis would have been missed.